Effect of Technological Characteristics of Various Types of Raw Materials on the Taste and Aroma of Sour Ales - Ponomareva O.; Borisova E.; Prokhorchik I. (Техника и технология пищевых производств)
Sour ales, traditionally produced in Belgium, Britain, and Germany, have gained wide popularity in America, Europe, and Russia. The paper provides generalized and systematized scientific data related to the technological and biotechnological characteristics of raw materials used in sour ales. The study featured malt, grain products (wheat, corn, rice, barley, rye, and oats), hop, Lactobacillus lactic-acid bacteria, Saccharomyces cerevisiae brewer’s yeast, and Brettanomyces yeast. Sour ales are usually prepared from a combination of different malts, such as Pilsner, Vienna, and Munich. Pilsner is used for malt type, while Munich is mostly employed as a basisfor dark varieties of sour ales. The review presents some of the flavor characteristics of malt types, as well as their recommended content. Unmalted grain products have a significant impact on the technological process and the organoleptic characteristics of acid ales. Unmalted wheat is used for Belgian sour ales, such as Lambic, Fruit Lambic, and Gueuze, in the amount of 30–40%, while 50 % are used in the German variety of Berliner Weiss. In general, the degree of wort pitching for sour ales should not exceed 8-15 IBU, since hop acids kill lactic-acid bacteria. Common hop varieties with a low or medium content of α-acids were found optimal for sour ale production. For example, for Flanders Red Ale, producers most often use one of the best traditional European varieties, namely Saazer (Zatetsky).The following types of homo- and heterofermentative lactic-acid bacteria are recommended for ale production technology: Lactobacillus delbrueckii, Lactobacillus brevis, Lactobacillus buchneri, Lactobacillus fermentum, and Lactobacillus plantarum. The aromatic characteristics of the wort fermented with lactic acid bacteria are described in the following terms: bread, yeast, honey, oil, cider, etc. Lactic acid bacteria are used in sour ales production, as well as Brettanomyces yeasts. Currently, brewing widely employstwo types of yeast: Brettanomyces bruxellensis and Brettanomyces anomalus. They give the drink a specific taste and aroma, due to hydroxycinnamic acids (HCAs) and esters (ethyl acetate, ethyl lactate, phenylacetate, etc.). The paper contains some practical recommendations on the use of specific types of raw materials to produce sour ales with a given sensory profile.